(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
The growth of female Islamist movements is part of the inevitable sociopolitical reality that forms part of the emerging political trend in the current global society. Islamist feminism, as it is called, undoubtedly impacts the politics of Indonesia from various angles that are worth further investigation. A thorough examination must be given to its interplay with other Indonesian political and religious bodies since it influences the country’s political ecosystem. Understanding their objectives, strategies, and prospective outcomes in Indonesia is critical for both government and civil society as they negotiate Indonesia’s changing political landscape. One prominent strategy this movement employs is digital personalization in digital space. Utilizing such a technique can be assessed as both an action and reaction toward the prevalent political discourse in Indonesia. The Islamist feminists have acknowledged insufficient coverage by the mainstream media on issues pertaining to women’s empowerment. Hence, it triggers the political consciousness of this movement to recalibrate the public sentiments toward the topic.